EFFORTS OF BHABINKAMTIBMAS THROUGH GUIDANCE AND COUNSELING IN THE PREVENTION OF THE CRIME OF CURANMOR AT TEGAL POLICE - AMRU JIHAD (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORTS OF BHABINKAMTIBMAS THROUGH GUIDANCE AND COUNSELING IN THE PREVENTION OF THE CRIME OF CURANMOR AT TEGAL POLICE AMRU AL JIHAD, 18.001, aaljihad20@gmail.com In this final project, the author raises the issue of "How are Bhabinkamtibmas' efforts in preventing the crime of theft through guidance and counseling at the Tegal Police Station?". Then it aims to describe the implementation of guidance and counseling by Bhabinkamtibmas and the efforts made by Bhabinkamtibmas in preventing activities through guidance and counseling. This study uses a qualitative approach with the type of field research, conducting limited observations, interviewing resource persons and document studies. In addition, the data used is also obtained from various references such as articles, journal books and relevant online media news. This study uses management theory, namely the functions and elements of management as well as the concepts contained in the laws and regulations governing the procedures for guidance and counseling. The author conducted research in the Legal Territory of the Tegal Police and the scope of the discussion was also limited according to the themes and topics taken by the author. The Binmas Unit of the Tegal Police on the issue of theft was not the main focus of the target activities and the material presented during guidance and counseling was not in accordance. Bhabinkamtibmas does not have a structured activity plan, apart from that, with the minimal number of Bhabinkamtibmas and having to concurrently hold many villages with limited budget conditions, this is also a problem for the Binmas Unit of the Tegal Police. From these problems, the leadership must take the initiative in making policies and innovating so that in carrying out their duties members can work effectively and efficiently and the results of their work can achieve the expected goals. Based on the existing problems, the authors present the data obtained at the time of the study. Then provide problem solving based on existing theories and concepts. At the end of writing the author pours some conclusions and suggestions in accordance with the discussion of the existing problems. Keywords: Binmas, Bhabinkamtibmas, Guidance, Counseling, Curanmor